Association between Polymorphisms in Vascular Endothelial Growth Factor Gene and Response to Chemotherapies in Colorectal Cancer: A Meta-Analysis. - Lei Wang; Shan Ji; Zeneng Cheng (PLoS ONE, 2015)
Some studies have investigated the effects of polymorphisms in the vascular endothelial growth factor (VEGF) gene on responsiveness to chemotherapy for colorectal cancer (CRC) and have shown inconclusive results.Eligible studies that assessed the associations between polymorphisms in the VEGF gene and response to chemotherapy in CRC were searched in the PubMed, Embase and Medline databases until November 2014. Odds ratios (OR) and 95% confidence intervals (CIs) were used to evaluate the associations, using Review Manager software, version 5.3. Stratified analysis was also conducted.In the overall analysis, a significant association with responsiveness to chemotherapy in CRC was identified in CC vs. CA of the VEGF -2578 C/A polymorphism (OR = 1.40, 95% CI 1.00-1.97, P = 0.05) and in CC+CT vs. TT of the VEGF -460 C/T polymorphism (OR = 0.71, 95% CI 0.53-0.96, P = 0.02). In subgroup analysis, a significant association was found in excluding anti-angiogenic agent subgroup in three comparison models of the VEGF -2578 C/A polymorphism and another three genetic models of the VEGF -460 C/T C/A polymorphism.CC vs. CA of the VEGF -2578 C/A polymorphism and CC+CT vs. TT of the VEGF -460 C/T polymorphism might be predictive factors of responsiveness to chemotherapy in CRC. However, single-nucleotide polymorphisms in the VEGF gene lacked sufficient predictive ability to determine whether patients with CRC should add anti-angiogenic agents to their chemotherapy regimens.